PENGARUH ZAKAT PERBANKAN, CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN UKURAN PERUSAHAAN TERHADAP KINERJA BANK UMUM SYARIAH (Studi Empiris Pada Bank Umum Syariah di Indonesia yang Terdaftar di OJK Periode 2015-2019) - Yulian, Tri Nurindahyanti; Rahman, Kristanti (JURNAL EKONOMI, 2021)
This study aims to determine the effect of Zakat on Banking, Corporate Social Responsibility (CSR) and company size on the performance of Islamic commercial banks registered with Bank Indonesia for 5 years from 2015-2019. The population of this research is Islamic banking which is registered with Bank Indonesia for the period 2015-2019. The sampling technique used purposive sampling method and obtained 6 Islamic Commercial Banks used as samples. The statistical analysis in this study used quantitative data.The results of this study indicate that: Zakat banking affects the performance of Islamic commercial banks, corporate social responsibility (CSR) affects the performance of Islamic commercial banks, company size affects the performance of Islamic commercial banks. Suggestions for futher research can add other social performance factors as independent or dependent variables such as ROE and ROI, because it is very likely that the influence could occur on other factors. Suggestions for banks need improvement in the publication of bank financial reports so that information hungry is more complete and in accordance with applicable regulations. Keywords: Zakat Banking, Corporate Social Responsibility (CSR), Company Size and Performance